SrTi1xNixO3 nanoparticles: synthesis and characterisation. (24th January 2011) - Phuong, Doan Thi Thuy; Hong, Le Van; Minh, Nguyen Van
We present the synthesis of SrTi1x Nix O3 (STNO) (x = 0.00, 0.10, 0.20, 0.30, 0.40, 0.50) nanoparticles and investigate their structure, absorption spectra, temperature-dependent Raman spectroscopy, impedance spectroscopy and magnetic property. Nanoparticles of STNO were prepared by sol-gel method. The particle size is smaller than 30 nm and depends on the Ni-substituted content. The experimental results indicate that the Ni ions have replaced the site of Ti in unit cells. Detailed temperature-dependent Raman studies of the optical phonons in STNO nanoparticles indicate that the mode energies and symmetry of SrTiO3 have been changed as doping of Ni ions. An abrupt change in Raman spectra suggests a phase transition around 150 K. We also used impedance spectra to discuss the conductivity of STNO in relation to absorption spectroscopy. Furthermore, magnetisation of STNO significantly increases as Ni content increases.